ICG/5-Fu coencapsulated temperature stimulus response nanogel drug delivery platform for chemo-photothermal/photodynamic synergetic therapy. (October 2021) - Yao, Shuting; Jin, Xiaokang; Wang, Cui; Cao, Ao; Hu, Jinhua; Chen, Biling; Wang, Bing
The multiple diagnosis and treatment mechanisms of chemotherapy combined with photothermal/photodynamic therapy have very large application prospects in the field of cancer treatment. Therefore, in order to achieve effective and safe antitumour treatment, it is necessary to design an intelligent responsive polymer nanoplatform as a drug delivery system. Herein, the thermosensitive poly-N-isopropylacrylamide (PNIPAM) nanogel particles were prepared by soap-free emulsion polymerization and loaded with a large amount of photosensitizer indocyanine green (ICG) and anticarcinogen 5-fluorouracil (5-Fu), which effectively to realize the cooperative chemotherapy and photothermal/photodynamic therapy for tumours. The 5-Fu@ICG-PNIPAM nanogels significantly improved the bioavailability of the drug and achieved controlled release. In addition, under near-infrared laser (NIR) irradiation at 808 nm, 5-Fu@ICG-PNIPAM nanogels generated lots of heat and reactive oxygen, which significantly enhanced cellular uptake and in vitro antitumour treatment effects. The results showed that 5-Fu@ICG-PNIPAM nanogels were effectively endocytosed by HeLa cells, which also enhanced the drug's entrance into the nucleus. Moreover, compared with alone chemotherapy or photothermal/photodynamic therapy, 5-Fu@ICG-PNIPAM nanogels significantly increased cytotoxicity under NIR irradiation, suggesting that chemotherapy and photothermal/photodynamic synergistic therapy had excellent antitumour properties. Therefore, this temperature-responsive nanogel platform probably has great application prospects in clinical antitumour treatment.